Classical and Bayesian Approach in Estimation of Scale Parameter of Nakagami Distribution - Kaisar Ahmad; S. P. Ahmad; A. Ahmed (Journal of Probability and Statistics)
Nakagami distribution is considered. The classical maximum likelihood estimator has been obtained. Bayesian method of estimation is employed in order to estimate the scale parameter of Nakagami distribution by using Jeffreys’, Extension of Jeffreys’, and Quasi priors under three different loss functions. Also the simulation study is conducted in R software.